Advancing Human Performance: Genomic Innovations and Ethical Imperatives in Sports Science - Kahrizi, Danial (International Journal of Sport Studies for Health, 2025)
The rapid convergence of genomic technologies and sports science is redefining the boundaries of human athletic potential. As a researcher at the intersection of molecular biology and sports medicine, I applaud your journal’s commitment to this transformative field and wish to expand upon critical developments in gene expression regulation, CRISPR-Cas9 applications, and next-generation sequencing (NGS) that demand scholarly attention and ethical scrutiny.